Оf environmental education among youth in activities environmental ngos republic of Poland - Гуран, Сергій Володимирович (Pedagogy of Higher and Secondary Education, 2013)
Guran S. V. Оf environmental education among youth in activities environmental ngos republic of Poland. This paper examines the influence of environmental ngos in the formation of environmental education among the younger generation in Poland. Analyzed the activity of the most prominent national environmental organizations that currently operate in Poland. The role of international, national and regional environmental organizations in the implementation of environmental education.